Management Physiotherapy With Modality Short Wave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), And Mc.Kenzie Exercise In Case Low Back Pain Et Causa Ischialgia - Zahrotul Umami; Heri Purnama Pribadi (Universitas Muhammadiyah Gresik, 2021)
Ischialgia is one of the manifestations of low back pain, pain appears along the root of thesciatic nerve, ischialgia caused by trauma that causes compression of the sciatic nerve. Physiotherapyas a health worker plays a role in reducing pain and improving the functional ability of patients who aredisturbe. The modalities used are short wave diathermy (SWD), transcutaneous electrical nervestimulation (TENS), and Mc Kenzie Exercise. The purpose of this study was to determine whether themodalities of short-wave diathermy (SWD), transcutaneous electrical nerve stimulation (TENS), and Mc.Kenzie exercise is can for reduce pain and improve the functional ability of impaired patients. The casestudy results showed a decrease in pain with the NRS scale for silent pain from 2 to 0, tenderness from6 to 3, pain in lumbar flexion from 3 to 0, pain in flexion and extension of the hip sinistra from 5 to 2, aswell as an increase in functional ability with there is a decrease in the Oswestry Index Disability scalefrom a total value of 17 = 37.80 % to 3 = 6.70%. The conclusion of this case study shows that themodalities of short-wave diathermy (SWD), transcutaneous electrical nerve stimulation (TENS), and McKenzie exercise are can reducing pain and improving functional ability.